Time course of auditory streaming: do CI users differ from normal-hearing listeners? - Böckmann-Barthel, Martin; Deike, Susann; Brechmann, André; Ziese, Michael; Verhey, Jesko L. (Frontiers in Psychology, 2014)
In a complex acoustical environment with multiple sound sources the auditory system uses streaming as a tool to organize the incoming sounds in one or more streams depending on the stimulus parameters. Streaming is commonly studied by alternating sequences of signals. These are often tones with different frequencies. The present study investigates stream segregation in cochlear implant (CI) users, where hearing is restored by electrical stimulation of the auditory nerve. CI users listened to 30-s long sequences of alternating A and B harmonic complexes at four different fundamental frequency separations, ranging from 2 to 14 semitones. They had to indicate as promptly as possible after sequence onset, if they perceived one stream or two streams and, in addition, any changes of the percept throughout the rest of the sequence. The conventional view is that the initial percept is always that of a single stream which may after some time change to a percept of two streams. This general build-up hypothesis has recently been challenged on the basis of a new analysis of data of normal-hearing listeners which showed a build-up response only for an intermediate frequency separation. Using the same experimental paradigm and analysis, the present study found that the results of CI users agree with those of the normal-hearing listeners: (i) the probability of the first decision to be a one-stream percept decreased and that of a two-stream percept increased as Δf increased, and (ii) a build-up was only found for 6 semitones. Only the time elapsed before the listeners made their first decision of the percept was prolonged as compared to normal-hearing listeners. The similarity in the data of the CI user and the normal-hearing listeners indicates that the quality of stream formation is similar in these groups of listeners.